ALKAPTONURIA - Javed, Mohammad; Khan, Imranullah; Afzal, Nadeem (Journal of Ayub Medical College Abbottabad, 1993)
Alkaptonuria, also termed ochronosis is a rare metabolic disorder due to a deficiency of the enzyme homogentisic acid oxidase12. Phenyl Alanine Tyrosine P-hydroxyphenyl pyruvic acid Homogentisic Maleylacetoacetic acid ` Further Catabolism The result of HGA oxidase deficiency is an accumulation of homogentisic acid in the body and its deposition preferentially in the cartilages, tendons and other tissues as a blue-black or a brown black pigment. HGA is also excreted in the urine turning it black if left to stand for a while.